Design of Semarang Denok Dance Robot Arm Movement Using STM32F103C8T6 Microcontroller - Hirkham Prayoga; Parama Diptya Widayaka (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2025)
Research and development of human robots continues to progress in Indonesia, one of which is through the Indonesian Robot Competition (KRI) organized by the Indonesian Talent Development Agency (BPTI) at the National Development Agency (Puspresnas) under the Ministry of Education, Culture, Research and Technology in the Republic of Indonesia. This event consists of several parts, including the Indonesian Robot Dance Competition (KRSTI). This study aims to design and implement a robotic arm movement system that is able to imitate the Denok dance movements, a typical Semarang dance, using the STM32F103C8T6 microcontroller. This project integrates robotics technology with local cultural arts as an effort to preserve culture through technological innovation. The system is designed using an XL-320 servo motor to produce precise movements that resemble human movements, while the STM32F103C8T6 microcontroller is used as the main control brain. The test results show that the robotic arm successfully imitates dance movements with a high level of precision and good synchronization. This study is expected to be the first step in the development of cultural arts-based robotics and encourage new innovations in preserving local culture. Keywords: Robotics, Denok dance, STM32F103C8T6, cultural preservation, robot technology.